'Marketless Trading in Hammurabi's Time': A Re-appraisal - Dale, Gareth (Journal of the Economic & Social History of the Orient, 2013)
In this article I revisit Karl Polanyi's writings on ancient Mesopotamia. I begin by situating them in the context of his general approach to trade, markets and money in the ancient world. Next, I reconstruct his major theses on Mesopotamia, drawing upon his published works as well as unpublished documents in the Karl Polanyi and Michael Polanyi archives. Finally, I provide a critical assessment of the merits and demerits of his contribution, with reference to Assyriological research published in the decades that have elapsed since his death in 1964.
History; Economics
Keywords: Mesoporamia; Mesopotamia; ancient history; assyriology; commerce; economic history; historiography; history; markets; money; trade

The boundaries of cosmopolitanism: Karl Polanyi and the 'Magyar-Jewish mongrel' - Dale, Gareth (Environment & Planning A, 2013)
The author offers his opinion on Hungarian historian Karl Polanyi and the views Karl expressed in a series of letters he sent to his brother Michael Polanyi. In these letters Karl wrote about the Germans attitude towards other Jews and the developing volatile social environment in Budapest, Hungary at the beginning of the 20th Century. He also wrote on the animosity between the Germans and the Jews.
Geography
Keywords: Baltic States; Germans; Jews; POLANYI; Michael; 1891-1976; biography; cosmopolitanism; history; social development